Doing criminological research: Affective states versus emotional reactions - Mercan, Boran Ali (Theoretical criminology, 2020)
Criminology has not yet adequately distinguished ‘emotional expression’ from ‘unconscious affect’. As a result, there are deficits in its understanding of criminal motivation. This article introduces a psychosocial approach that reveals the unconscious affects that are hidden within offender discourses. To do so it draws on Freud’s psychoanalytical account of affects and thus allows for an understanding of the energies and fantasies that lurk behind them. Using examples from crime ethnographies and restorative justice conferences, the article demonstrates that this theoretical orientation and these methods allow the criminologist to engage with the inner-world of offenders more deeply. Doing so, for example, shows that emotional reactions of offenders, in fact, fantasmatically conceal the latent negativity of anxiety and the fear of violent humiliation. Through establishing ‘affect’ as a more distinct analytic within criminology, its theoretical and methodological tool-box is significantly enhanced.